Post-activation Potentiation Response of Climbers Performing the Upper Body Power Exercise - Sas-Nowosielski, Krzysztof; Kandzia, Klaudia (Frontiers in Psychology, 2020)
The purpose of this study was to determine a performance-enhancing effect of post-activation potentiation (PAP) stimulus on climbing-specific upper body power exercises, measured by the IRCRA Power Slap test on a campus board. Two groups of climbers performed the test under one of two conditions: without initial pre-loading (control group) or after 5RM (repetition maximum) pull-ups (PAP group). The test was performed at four time points: at baseline (PRE) and after 4 (POST4), 6 (POST6), and 8 (POST8) minutes of a PAP stimulus (PAP group) or after the same rest period lengths (control group). The results showed that post-baseline slap distances were significantly greater in the experimental group while no change was seen in the control group [repeated measures ANOVA: F(3,42) = 6.26, p = 0.001]. Post hoc analysis revealed no significant difference between any of the post-baseline trials in both groups. The mean improvement in the first POST4 test in the experimental (PAP) group was +6.5 cm (6.8%). The results of the present study suggest that PAP might be beneficial for acute improvement of upper body power performance in climbers. Therefore we conclude that such stimuli might be advisable for climbers as a part of the warm-up before bouldering competitions and training as well. They might also offer a stronger stimulus for climbers working on power development.